"WONDER IS THE TRUTH OF ENLIGHTENMENT" - Uldona Abdurahmonova (Academia Science Repository, 2023)
In this article, the interpretations of the phenomenon of wonder, which is considered the primary basis for a person’s recognition of the Creator, identity and existence, in the works of Socrates, Plato, Aristotle and Alisher Navoi.